Nanocellulose from Curava Fibers and their Nanocomposites - Souza, Sivoney Ferreira [UNESP]; Leão, Alcides Lopes [UNESP]; Cai, Jenny Hui; Wu, Crystal; Sain, Mohini; Cherian, Bibin Mathew (Taylor & Francis Ltd, 2010)
Cellulose nanofibres are environmentally benign and have unique features compared to macro scales. Nowadays, many efforts have been made in developing potential composite products with improved properties. However, the manufacturing of nanocomposites with natural fibres has been a challenging task due to the difficulty encountered in order to aggregate the nanofibres. In this paper, curaua fibres were utilized for isolation of nanofibres. Polyvinylalcohol (PVA) was chosen as the matrix due to its excellent film forming, packaging capacity and its hydrophilic nature, which enhances the interfacial compatibility between the natural fibre and the matrix. The composite is prepared by solution casting technique.
Keywords: Curaua; nanocellulose; nanocomposites; polyvinylalcohol